Pelatihan Keterampilan Herbarium Kering Modern bagi Guru dan Siswa di SMK Negeri 2 Batu - Tintrim Rahayu; Ari Hayati (University of Merdeka Malang, 2020)
Batu as a tourism city produces a lot of vegetables, flowers, and ornamental plants. Many cut flower waste from sorting is not suitable for sale. Meanwhile, SMK Negeri 2 Batu has developed several products to be marketed and is a place for students to study entrepreneurship. However, there are problems in getting market demand due to intense competition. Therefore, production requires continuous innovation and creativity. This new method is offered to increase grades by teaching them the skills of a modern dry herbarium using waste flowers from the surrounding environment. The purpose of this activity is that the teachers and students of SMK Negeri 2 Batu have the knowledge and skills to create a modern dry herbarium with Oshibana techniques. Teaching is done by giving lectures, demonstrations, practices, and evaluations. The results show increased knowledge to utilize flower and leaf waste through manufacturing activities of modern dried herbarium with the Oshibana technique. The program also provides counseling on how to use wasted flowers and leaves that can be done properly. The training to make a modern dry herbarium which was later named